Characterization of the Epstein-Barr virus (EBV) DNA methylation status in blood circulating cell-free DNA. - Woo, Wan Lu. (2012)
Background: Real time PCR detection of cell free circulating Epstein-Barr virus (EBV) DNA is a sensitive and specific tool to screen and to monitor the treatment of EBV associated malignancies. QIAamp® DNA Blood kit is widely used for DNA extraction despite its low extraction efficacy. This study aims to evaluate the efficacy of three commercial DNA extraction kits and to quantify methylation status of cell free circulating EBV DNA in nasopharyngeal carcinoma patients.